Biossorção em sistema multielementar dos íons Pb2+, Cu2+, Ni2+, Cd2+ e Zn2+ em solução aquosa usando a vagem seca do feijão (Phaseolus vulgaris L.) modificada: otimização usando planejamento fatorial - Raulino, Giselle Santiago Cabral (2016)
The solid waste coming from agro-industries have been extensively studied as potential adsorbents for the treatment of environmental pollutants, as an alternative to traditional treatment methods. In order to improve the adsorption capacity of these materials, several chemical modifications are studied in the literature. In this context, this study aimed to investigate the process of acid modification of dry bean pod (Phaseolus vulgaris L.) after alkaline pretreatment using tannic acid (FAT), polyacrylic (FPACRIL) and polyacrylic-co acrylamide (FPAA) and evaluate their performances as adsorbents for the removal of Pb2+ Cu2+, Cd2+, Ni2+ and Zn2+ metal ions in multielement aqueous solution. For this the factorial design was used as a tool both in the stage of study of the variables that affect the modification process as the optimization stage of the adsorptive process. In the modifying step, it was observed that only the variable pH had a significant effect on the modification process with tannic acid. When the modifying agent was the polyacrylic acid both variable initial concentrations as weight were significant, while the temperature was the only significant variable in the modification with polyacrylic-co-acrylamide acid. The removal percentage of all metal ions from aqueous solutions increased on average by 45% after modification with the three acids. The best materials obtained in the modification step for the three acids were characterized and the analysis showed that the soluble lipid fraction was removed after the alkali treatment, improving the availability of adsorbent sites. The materials from the three modification showed good thermal stability to about 200°C and no morphological changes. The point of zero charge were between 2.91 and 3.59. The study of the process of the variables that influence the adsorption capacity was conducted in two stages. First a fractional experimental design was carried and was observed that the variables pH, initial concentration and mass of adsorbent were the most significant variables in the adsorption capacity of the materials studied for almost all metal ions. Then an optimization using a central composite design was performed. From the design, the quadratic models were obtained and the response surfaces were constructed for the three modified materials. The best conditions found for removal of five multi metals were: pH = 3.5; adsorbent mass = 200 mg; initial concentration of metal ions = 4.5 mM, for the three materials. The values predicted by the models in the optimized conditions were compared with experimental results and were statistically equal to the three materials. Of the three materials obtained, the dry bean pod modified with tannic acid (FAT) showed the best performance, achieving the removal of 1.0 mmol / g. Then FAT has been used in studies of kinetics and adsorption isotherm. The kinetic study indicated equilibration time of 2 hours, with the model of pseudo-second order been the best model that fit to the data. The experimental adsorption isotherm data set both the Langmuir model as the Freundlich. FAT material was compared to a commercial adsorbent (activated charcoal) featuring superior performance, resulting in adsorption capacity 75% greater than the capacity of the commercial material